2016
DOI: 10.1002/fsn3.399
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the proximate composition, antioxidant potential, and antimicrobial activity of mango seed kernel extracts

Abstract: After pulp extraction in fruit processing industry, a significant quantity of mango seed kernels are discarded as solid wastes. These seed kernels can be ideal raw materials for obtaining extracts rich in bioactive compounds with good antioxidant properties. The conversion of these wastes into utilizable food ingredients would help in reducing environmental problems associated with processing waste disposal. In order to determine their potential use, this study evaluated some of the biochemical characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
46
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 23 publications
10
46
2
3
Order By: Relevance
“…This is may be due to that MSK could be used as antimicrobial compounds due to its high quality of fat and protein as well as high levels of natural antioxidants. Similar results were obtained when counting Psychrophilic and Coliform bacteria in fresh breast and thigh meat ( et al, 1986) and antibiotics against pathogenic microorganism (Mutua et al, 2017). Table 9 showed the economic efficiency of using mango seed kernel (MSK) as a partial replacement of corn for growing Gimmizah cockerels.…”
Section: Microbiological Parameterssupporting
confidence: 74%
See 1 more Smart Citation
“…This is may be due to that MSK could be used as antimicrobial compounds due to its high quality of fat and protein as well as high levels of natural antioxidants. Similar results were obtained when counting Psychrophilic and Coliform bacteria in fresh breast and thigh meat ( et al, 1986) and antibiotics against pathogenic microorganism (Mutua et al, 2017). Table 9 showed the economic efficiency of using mango seed kernel (MSK) as a partial replacement of corn for growing Gimmizah cockerels.…”
Section: Microbiological Parameterssupporting
confidence: 74%
“…Additionally, the highest IgG and IgM values were recorded for cockerels fed diet containing the lowest MSK level (10%). The improvement in immunological status in the current results may be attributed to the MSK contains various phenolic compounds which considered as antimicrobial, antifungal, antiviral (Cojocaru et al, 1986) and antibiotics against pathogenic microorganism (Mutua et al, 2017). Results of Table 6 indicated that there was a significant decrease (p≤0.05) in plasma cholesterol by increasing MSK levels as a replacement of corn compared with the control group.…”
Section: Biochemical Parametersmentioning
confidence: 55%
“…Mutua et al. () reported that the percentage scavenging ability of mango kernel extracts at a concentration of 20 mg/mL from various mango cultivars was 92.2%.…”
Section: Resultsmentioning
confidence: 99%
“…The oxidative stability and antioxidant potential of MSKF may be partly attributed to the presence of tocopherols naturally present in mango seed fat (Jahurul et al, 2017;Kittiphoom, 2012). Mutua et al (2017) reported that the percentage scavenging ability of mango kernel extracts at a concentration of 20 mg/mL from various mango cultivars was 92.2%.…”
Section: Antioxidant Assaysmentioning
confidence: 99%
“…Dado lo anterior, en este estudio se analizó la composición química y la actividad antibacteriana del aceite esencial obtenido de las hojas de la especie M. indica L., las cuales fueron recolectadas en tres regiones de la República Bolivariana de Venezuela. La investigación se basó en la descripción de la actividad antibacteriana en los extractos obtenidos de diferentes partes de la planta de M. indica L. [9][10][11][12][13][14], con el objetivo de contribuir con la caracterización de esta especie. Este es el primer estudio comparativo acerca de la actividad antibacteriana del aceite esencial procedente de las hojas de M. indica L. de tres regiones de Venezuela.…”
Section: Introductionunclassified